VALUE CHAIN ANALYSIS AND MARKETING STAKEHOLDERS OF BALI CATTLE IN KUPANG REGENCY AND CITY - Ninu, Andy; Jacob, Jois Moriani; Bele, Agrippina; Vertygo, Stormy (Buletin Veteriner Udayana, 2026)
Bali cattle are one of the primary commodities of Timor Island, Indonesia, and they contribute substantially to the community’s income. This is demonstrated by the substantial increase in the cattle population over the past three years, as well as the heightened demand for beef both within Timor Island and beyond NTT. This study aimed to analyze the marketing value chain of Bali cattle for each stakeholder within Kupang City and District and identify the specific function of each participant in this value chain. This research methodology is descriptive, specifically employing a case study approach that encompasses interviews with all participants involved in the marketing of Bali cattle, along with stakeholder analysis derived from the interview findings. The analysis revealed six key business actors contributing to the value-added process of cattle sales: suppliers, producers, collectors, traders, processors, and retailers. Additionally, five influential entities—government agencies, financial institutions, non-governmental organizations (NGOs), institutions of higher education, and animal insurance providers—were identified as participants in this value chain. Influencers possess distinct duties and responsibilities that collectively enhance the Bali cattle value chain within Kupang City and the District. However, government authorities at both the national and local levels are one of the principal stakeholders exerting significant influence over the value chain. Based on the outcomes of the stakeholder/business actor analysis, the most important role in enhancing beef sales value was at the processing stage (44%), followed by suppliers (19%), retailers (17%) and producers (14%). Conclusion: Six business actors within the livestock sector each fulfil distinct duties and contribute value at every stage of the Bali cattle sales value chain, influencing fluctuations in the selling prices of Bali cattle and their products in Kupang City and District. Recommendation: Future research should integrate several critical and interrelated factors within a comprehensive value chain analysis, with a specific emphasis on constructing a value chain database for the Kupang city and district.